2006
DOI: 10.1038/modpathol.3800492
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepatocyte nuclear factor-1beta (HNF-1beta) in clear cell tumors and endometriosis of the ovary

Abstract: Clear cell tumors of the ovary are frequently associated with ovarian endometriosis. Clinicopathologically, it has been suggested that clear cell tumors develop from endometriosis, but there has been little molecular evidence supporting this speculation. Microarray analysis revealed recently that hepatocyte nuclear factor1beta (HNF-1beta) was significantly upregulated in clear cell carcinoma of the ovary. In the present study, we examined 30 clear cell tumors (26 malignant, three borderline, and one benign) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
156
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(176 citation statements)
references
References 16 publications
13
156
0
3
Order By: Relevance
“…Among them, hepatocyte nuclear factor 1 beta (HNF1b) seems to be the best because of its high sensitivity and specificity. 32,33 However, one study reported HNF1b positivity in the nuclei of normal and tumor cells in the endometrium, 34 and the establishment of other markers may also be useful for differential diagnosis of clear cell adenocarcinoma. Annexin-A4, 35,36 HOXA10, 37 phospho-serine aminotransferase, 36 and glypican 3 38 are all suitable candidates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, hepatocyte nuclear factor 1 beta (HNF1b) seems to be the best because of its high sensitivity and specificity. 32,33 However, one study reported HNF1b positivity in the nuclei of normal and tumor cells in the endometrium, 34 and the establishment of other markers may also be useful for differential diagnosis of clear cell adenocarcinoma. Annexin-A4, 35,36 HOXA10, 37 phospho-serine aminotransferase, 36 and glypican 3 38 are all suitable candidates.…”
Section: Discussionmentioning
confidence: 99%
“…However, five of the eight cases with both endometriosis and clear cell adenocarcinoma, the atypical and normallooking epithelium at the surface of the endometriotic cysts showed at least focal napsin A positivity. As positive expression of HNF1b is reported in the nuclei of the epithelial cells in the majority of the cases with endometriosis, 33 it is possible that napsin A may have a different role than HNF1 b in ovarian clear cell adenocarcinoma tumor cells. However, further analysis using more cases is necessary for clarification.…”
Section: Discussionmentioning
confidence: 99%
“…11 It was also subsequently reported to be positive in areas of endometriosis or endometriotic epithelium in a study of ovarian clear cell carcinoma lending molecular support for the hypothesis that the concurrent endometriosis seen in ovarian clear cell carcinoma may be linked as a precursor lesion. 12 The significance of clear cell carcinoma as an entity in pancreatic cancers is inadequately characterized. Our study of 84 archived cases of diagnosed pancreatic adenocarcinomas has uncovered the largest known report of a clear cell phenotype consisting of at least 75% of the tumor.…”
mentioning
confidence: 99%
“…Their POU S domains have at least one additional α-helix at the N-terminus, and the second † This work was funded by the Juvenile Diabetes Research Foundation (1-2004-506) (8,24). Recently, HNF1β has also been associated with ovarian clear cell carcinoma (25,26), and mutations in this protein are also responsible for neonatal cholestatic jaundice (27). Thus, in addition to its effect on pancreatic β-cells (5,28,29), HNF1β appears to be involved in normal functioning of many other organs (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Even though mutations in both are associated with diabetes, renal developmental disorders and genital malformations are more prominent with the mutations in HNF1β (7,8), which also encompass a wide clinical spectrum including genital tract malformations, abnormal liver function, pancreatic atrophy, exocrine insufficiency, and biliary manifestations (8,24). Recently, HNF1β has also been associated with ovarian clear cell carcinoma (25,26), and mutations in this protein are also responsible for neonatal cholestatic jaundice (27). Thus, in addition to its effect on pancreatic β-cells (5,28,29), HNF1β appears to be involved in normal functioning of many other organs (10,11).…”
mentioning
confidence: 99%